The Efficacy and Potential Mechanisms of Metformin in the Treatment of COVID-19 in the Diabetics: A Systematic Review - Zangiabadian, Moein; Nejadghaderi, Seyed Aria; Zahmatkesh, Mohammad Mahdi; Hajikhani, Bahareh; Mirsaeidi, Mehdi; Nasiri, Mohammad Javad (Frontiers in endocrinology (Lausanne), 2021)
Diabetes mellitus (DM) is one of the most common comorbidities among patients with coronavirus disease 2019 (COVID-19) which may exacerbate complications of this new viral infection. Metformin is an anti-hyperglycemic agent with host-directed immune-modulatory effects, which relieve exaggerated inflammation and reduce lung tissue damage. The current systematic review aimed to summarize the available evidence on the potential mechanism of action and the efficacy of metformin in COVID-19 patients with DM. A systematic search was carried out in PubMed/Medline, EMBASE, the Cochrane Controlled Register of Trials (CENTRAL), and Web of Science up to July 30, 2020. The following keywords were used: "COVID-19", "SARS-CoV-2", "2019-nCoV", "metformin", and "antidiabetic drug". Fourteen studies were included in our systematic review. Three of them were observational with 6,659 participants. Decreasing insulin resistance, reduction of some inflammatory cytokines like IL-6 and TNF-α, modulation of angiotensin-converting enzyme 2 (ACE2) receptor, and improving neutrophil to lymphocyte ratio are some of the potential mechanisms of metformin in COVID-19 patients with DM. Nine out of fourteen articles revealed the positive effect of metformin on the prognosis of COVID-19 in diabetic or even non-diabetic patients. Moreover, different studies have shown that metformin is more effective in women than men. The use of metformin may lead to improve the clinical outcomes of patients with mild to moderate SARS-CoV-2, especially in diabetic women. Further observational studies should be conducted to clarify the effects of metformin as a part of the treatment strategy of COVID-19.